2008
DOI: 10.1002/pon.1387
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in young families: a qualitative interview study of fathers and their role and communication with their children following the diagnosis of maternal breast cancer

Abstract: This study suggests that clinicians could improve their care of breast cancer patients by being more family-centred. Fathers routinely need more information and preparation about the likely impact of the illness and its treatment (especially side effects) on the mother, and how children of different ages may react to the emotional strain. Clinicians need to be prepared to offer to talk to teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 23 publications
4
87
0
14
Order By: Relevance
“…They told their parents and clinicians that they were satisfied with their direct engagement, without parents present, with the specialists because in this way they felt they were an important part of the family system and they understood that in their families no lies were being told about the illness and so they could trust their parents. Some studies underline that communication and expressiveness in families can be identified as a key issue in children's positive coping with parental illness [10,13]. Our findings in fact underlined the absence of psychological problems in children after the intervention.…”
Section: Discussionsupporting
confidence: 55%
“…They told their parents and clinicians that they were satisfied with their direct engagement, without parents present, with the specialists because in this way they felt they were an important part of the family system and they understood that in their families no lies were being told about the illness and so they could trust their parents. Some studies underline that communication and expressiveness in families can be identified as a key issue in children's positive coping with parental illness [10,13]. Our findings in fact underlined the absence of psychological problems in children after the intervention.…”
Section: Discussionsupporting
confidence: 55%
“…However, despite a wide-ranging literature search supported by an information specialist, we found little research on the subsequent process -when patients tell family members/friends their bad news. A few studies have explored communicating a parental cancer diagnosis to children and adolescents [13,14], particularly in relation to breast cancer [15][16][17] and genetic risk for cancer [18][19][20]. However there is a dearth of literature relating how patients relay bad news of a cancer diagnosis to adult significant others, what we refer to here as sharing bad news.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have reported that more than a quarter of women diagnosed with breast cancer have children living at home (Bloom & Kessler, 1994) and these mothers tend to experience difficulties in meeting the needs of their children in addition to their own needs (Dunn & Steginga, 2000). In families with children living at home, the partner may have to take responsibility for organizing the day-to-day lives of their children, meeting their emotional as well as physical needs (Forrest, Plumb, Ziebland, & Stein, 2009). While most mothers and fathers want to keep life "normal" for their children (Forrest et al, 2009;Stiffler, Haase, Hosei, & Barada, 2008), this may not be possible during treatment and couples could get totally overwhelmed, feeling isolated and helpless, with increased parental responsibilities on top of everything else (Rayson, 2001).…”
Section: Couple Relationships After a Diagnosis Of Breast Cancermentioning
confidence: 99%
“…In families with children living at home, the partner may have to take responsibility for organizing the day-to-day lives of their children, meeting their emotional as well as physical needs (Forrest, Plumb, Ziebland, & Stein, 2009). While most mothers and fathers want to keep life "normal" for their children (Forrest et al, 2009;Stiffler, Haase, Hosei, & Barada, 2008), this may not be possible during treatment and couples could get totally overwhelmed, feeling isolated and helpless, with increased parental responsibilities on top of everything else (Rayson, 2001). Reviews of studies on parents' experience following a diagnosis of cancer have revealed themes that are important to parents, such as being a good parent, telling the children, and maintaining routine at home, highlighting their support needs (Semple & McCance, 2010).…”
Section: Couple Relationships After a Diagnosis Of Breast Cancermentioning
confidence: 99%